Peran Mindfulness dalam Memaafkan Ruminasi Masa Lalu - Maulaya, Fahdina; Baroroh, Nurin (Lembaga Yasin AlSys, 2025)
This study aims to analyze the role of mindfulness in helping individuals forgive without having to forget traumatic experiences, as well as in reducing rumination related to the past. Although mindfulness has been proven effective in altering negative thinking patterns, understanding of how mindfulness contributes to the acceptance of the past and the management of negative emotions remains limited. This research was conducted at the Darussalam Counseling Center, Blokagung, Banyuwangi, which integrates spiritual-based approaches with mindfulness practices. A qualitative method with a case study design was employed to explore the experiences of individuals participating in mindfulness therapy. Data were collected through in-depth interviews and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that mindfulness significantly helps individuals reduce the intensity of rumination, enhance self-acceptance, and shift their paradigm of forgiveness. Individuals practicing mindfulness learn to observe thoughts without emotional attachment, accept their imperfections, and release emotional burdens from the past without having to forget traumatic experiences. In conclusion, mindfulness plays an important role in accelerating emotional healing, building psychological well-being, and enhancing the ability to forgive with full awareness. The implication of this study is the need to integrate mindfulness techniques into counseling programs, particularly for individuals with emotional trauma, to help them develop healthier and more sustainable coping mechanisms.